Fluoride dose response in pH-cycling models using bovine enamel - Vieira, AED; Delbem, ACB; Sassaki, K. T.; Rodrigues, E.; Cury, J. A.; Cunha, Robson Frederico [UNESP] (Karger, 2005)
The aim of this study was to establish methodologies for verification of the fluoride solution dose-response relationship using bovine enamel and pH-cycling models. Six models of the cariogenic challenge were performed, varying the time of demineralization and pH, time of remineralization, composition of de- and remineralization solutions, frequency and time of application of treatment solutions and pH-cycling duration. For the evaluation of the fluoride effect on caries dynamics, two proposed models provided for improvement in standardization of methods leading to a higher level of precision, demonstrating a dose response between treatments with regard to surface microhardness and Delta Z. For the evaluation of the fluoride effect on enamel remineralization, the addition of fluoride to the de- and remineralization solutions and the reduction of frequency and time of application of fluoride solutions led to a more suitable pH-cycling model. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: fluoride effect on caries dynamics; fluoride effect on enamel remineralization; microhardness analysis; in vitro pH-cycling models; bovine enamel; topical fluoride; fluoride solution dose-response relationship